"دراسة استكشافية لواقع المحاسبة البيئية في الجزائر *دراسة حالة في شركة المذابح الملكية بالوادي*" - نجاة, علاهم; خديجة, غزال; اسراء, شويرف; ايناس, صالحي (University of eloued جامعة الوادي, 2021)
"تهدف هذه الدراسة إلى استكشاف واقع المحاسبة البيئية في الجزائر بحيث اعتمدنا على المنهج الوصفي و دراسة حالة في شركة المذابح الملكية بالوادي ، و نتيجة لتطور الاقتصادي الذي اثر بدوره على تجديد الأنظمة المحاسبية المالية و المعايير الدولية من جهة و ضغوطات الدولة للحد من تلوث المحيط البيئي الذي تسببه المؤسسات الاقتصادية من جهة أخرى . لقد توصلت الدراسة إلى الأهمية البالغة لمحاسبة التكاليف البيئية في شركة المذابح الملكية بالوادي ، حيث قامت باستثمارات بيئية عديدة كتركيب مصفاة للمياه الباطنية ، محطة معالجة المياه المستعملة بعد الجزارة ، محرقة للقضاء على النفايات و مصاريف أخرى للمحافظة على البيئة ، حيث حققت من ذلك عوائد كإعادة بيع المخلفات و تخفيض مصاريف استهلاك المياه ، كما تمت معالجة التكاليف البيئية وفقا للنظام المحاسبي المالي . يستحسن خلق نظام محاسبي بيئي الذي يساعد الشركة على دقة الاعتراف بمسؤوليتها البيئية من خلال الإفصاح عن تكاليفها البيئية و قياسها لتقوية وجودها في المحيط الاقتصادي و البيئي . ""This study aims at investigation the reality of Envirronmenntal Accounting in Algeria , we relied on The Observvation Method to study the state of The Royal Slaughterhouse company as an example of Economicc Instittuutions in Algeria . As result of the economic development that has in turn affected the renewal of accounting systems and internationg standards from one side . and governmental pressures to control environment pollution that is caused by economic institutions on The other side . the study realized the great importance of accounting environmental costs to The Royal Slaughterhouse company of El-Oued . The company has done severl environmental investments . such as setting up ground water filters . a slaughterhouse wastewater treatment plant. An incinerator for waste disposal and other expenses for preserving the environment . from which revenues were made as in reselling waste and reducing water expenses . as well as addressing environmental expenses according to The Financial accounting System . It is recommended to create an environmental accounting system that helps companies maintain precise recognition of their environment responsibilities through the disclosure and the measuring of its environmental costs . to strengthen its presence in the economic and environmental spheres . "
ماستر محاسبة وتدقيق
Keywords: المحاسبة البيئية , التكاليف البيئية , قياس التكاليف البيئية.; environmental accounting , environmental costs and measuring environmental costs .